Addressing Distance Learning Barriers in Indonesia Amid the Covid-19 Pandemic - Nadia Fairuza Azzahra (Center for Indonesian Policy Studies (CIPS), 2020)
Covid-19 pandemic has caused millions of Indonesian students unable to continue their learning activity in schools and rely on technology to support distance learning. However, uneven access to the internet, disparity in teacher qualifications and education quality, and the lack of ICT skills appeared as the biggest challenges in implementing distance learning. This latest policy brief outlines vulnerabilities in Indonesia's distance learning efforts and actions that have been taken by the government and private sectors. There are six policy recommendations for the Indonesian policymakers that aim to improve the implementation of distance learning during the pandemic.
Keywords: 330; covid-19; covid19; corona virus; nadia fairuza; distance learning; online learning; low cost private schools